The hidden cost of global economic integration: How foreign investment drives military expenditures. (January 2023) - Kentor, Jeffrey; Clark, Rob; Jorgenson, Andrew
Highlights: This is the first published study on the impact of global foreign investment networks on military expenditures. Our study creates a global foreign direct investment network for 129 countries between 2001 and 2017. We find that degree centrality in the global FDI network has a positive impact on military expenditures from 2001 to 2017. We estimate that this global corporate activity increased worldwide military expenditures by about US$ 134 billion dollars over this period. Abstract: The global economy is increasingly integrated, with more than 60, 000 international firms now directing almost one million foreign affiliates worldwide. We examine one significant, and largely unexplored, aspect of this integration – the cost of protecting these global investments. More specifically, we assess the extent to which foreign direct investment (FDI) drives military expenditures. Drawing from recent studies, we adopt a social network framework. Using data from the United Nations Conference on Trade and Development's Bilateral FDI Statistics and the International Monetary Fund's Coordinated Direct Investment Survey, we construct the global FDI network between 2001 and 2017 and derive out-degree centrality scores based on each country's structural location in this network. Next, using data from the Stockholm International Peace Research Institute, we estimate two-way fixed effects models for a global sample of 1, 880 observations across 129 countries over this time period to assess the relationship between FDI centrality and military expenditures. We find that degree centrality in the global FDI network has a positive impact on military expenditures, net of other relevant predictors. Military expenditures do not, however, appear to drive FDI. We estimate the aggregate impact of FDI centrality on military expenditures, and suggest that these increased costs amount to a hidden subsidy of global corporate activity.